“Laying bricks to build integrated career guidance plans”: Best practices in vocational education and training in Andalusia, Spain - Romero-Rodríguez, Soledad; Moreno-Morilla, Celia; Mateos-Blanco, Tania (Frontiers in Psychology, 2022)
Vocational Education and Training (VET) policies are paying increasing attention towards the need to develop quality career guidance processes. Career guidance plays an essential role in this challenge by enabling people to develop the career management skills that allow them to become aware of their full potential and to build life projects that facilitate the emotional management of uncertainty and complexity, participating as responsible agents in their environment. After conducting a literature review on each of these key elements, we set out to identify best practices in VET as "building blocks" for the construction of an integrated career guidance plan in VET. This study adopts an approach based on qualitative methodology, specifically a documentary type of research has been carried out. The documents analyzed correspond to 88 good practices identified in Andalusia (Spain). The analysis strategy used was a content analysis. For this purpose, a system of categories has been designed, from a deductive perspective, which has contributed to a systematic analysis of them. One of the first conclusions of the study is the uneven development o best practices in the different VET professional pathways. The practices carried out in the centres begin to incorporate different elements and thus facilitate the creation of a suitable context for the development of comprehensive career guidance plans in VET. The article closes by offering implications for the development of guidance in the education system (at VET level) and discusses lines of future research.